'Appeals to nature' in marriage equality debates: A content analysis of newspaper and social media discourse. (27th February 2017) - O'Connor, Cliodhna
Abstract : In May 2015, Ireland held a referendum to legalize same‐sex marriage, which passed with 62% of the vote. This study explores the role played by 'appeals to nature' in the referendum debate. Little research has investigated how biological attributions are spontaneously generated in real‐world discourse regarding sexual rights. Through content analysis of newspaper and Twitter discussion of the referendum, this study aims to (1) establish the frequency of appeals to nature and their distribution across the various 'sides' of the debate and (2) analyse the forms these natural claims took and the rhetorical functions they fulfilled. Appeals to nature occurred in a minority of media discussion of the referendum (13.6% of newspaper articles and .3% of tweets). They were more prominent in material produced by anti‐marriage equality commentators. Biological attributions predominantly occurred in relation to parenthood, traditional marriage, gender, and homosexuality. The article analyses the rhetorical dynamics of these natural claims and considers the implications for marriage equality research and activism. The analysis suggests appeals to nature allow anti‐marriage equality discourse adapt to a cultural context that proscribes outright disapproval of same‐sex relationships. However, it also queries whether previous research has overemphasized the significance of biological attributions in discourse about groups' rights.